2010
DOI: 10.1375/aedp.27.1.31
|View full text |Cite
|
Sign up to set email alerts
|

Strategy Use by English-Major Jordanian Undergraduates

Abstract: Research suggests that gender and perceived language proficiency level are among the factors that may impact the strategies language learners use. This study explored the impact of these variables on learning strategies used by 111 English-major Jordanian students. The instrument was Oxford's (1990) Strategy Inventory for Language Learning (SILL). The study revealed that females opt to use strategies more frequently than males. Results also showed that the higher the proficiency level, the more frequent the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
1
2
0
Order By: Relevance
“…This accords with relevant literature indicating that, compared to males, females are more efficient language learners (Al-Shaboul, Asassfeh, & Alshboul, 2010;Ehrman & Oxford, 1989;Green & Oxford, 1995;Hong-Nam & Leavell, 2006;Oxford, 1993;Politzer, 1983). Additionally, particularly in the context of this study, the majority of the English-majors are females, which entails having a wider space for socialisation and saving a stage for language practice.…”
Section: Discussionsupporting
confidence: 87%
“…This accords with relevant literature indicating that, compared to males, females are more efficient language learners (Al-Shaboul, Asassfeh, & Alshboul, 2010;Ehrman & Oxford, 1989;Green & Oxford, 1995;Hong-Nam & Leavell, 2006;Oxford, 1993;Politzer, 1983). Additionally, particularly in the context of this study, the majority of the English-majors are females, which entails having a wider space for socialisation and saving a stage for language practice.…”
Section: Discussionsupporting
confidence: 87%
“…Unlike the findings of El-Dib ' (2004) and Abu-Radwan's (2011) studies, other studies listed in Table 1 (e.g., Alhaysony, 2017;Ismail & Al-Khatib, 2013;Shmais; showed no significant differences between male and female participants in terms of their overall LLS use. Conversely, Alhaisoni (2012) and Al-Shaboul et al (2010) who collected their data using Oxford's (1990) SILL found that their female university students from Saudi Arabia and Jordan respectively reported using more LLSs, especially social strategies, than their male peers. Table 1 also reveals that almost all the quantitative studies (e.g.…”
Section: Language Learning Strategy Research Into Arab Learners Of Enmentioning
confidence: 99%
“…In the Jordanian Arabic context, Alshboul, Alshboul & Asassfeh (2010) examined how some lexical words developed to serve future markers in Jordanian Arabic. The study proposed that the lexical word bad(di) evolved into the future marker b(a)-.…”
mentioning
confidence: 99%